PEMANFAATAN MEDIA PEMBELAJARAN VIDEOSCRIBE SEBAGAI ALTERNATIF PEMBELAJARAN DARING BAHASA INDONESIA DI SMKN 1 CANGKRINGAN - YUNIASIH YUNIASIH (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2022)
Interaction in online learning is very limited so educators must be creative and innovative in choosing learning media, especially in Indonesian subjects in order to improve student learning outcomes at home. The application of videoscribe learning media in Indonesian online learning is one of the uses of animation-based learning media technology that is in accordance with the times so that it is expected to improve the quality of education. The purpose of this best practice is to describe the use of the videoscribe learning media as an alternative to online learning Indonesian class XI at SMKN 1 Cangkringan. The best practice was carried out in November, Odd Semester of the 2020/2021 Academic Year with 66 students as research subjects. The purpose of this scientific paper is to describe the improvement of learning outcomes by utilizing videoscribe learning media technology as an alternative online learning media in Indonesian subjects. The application of videoscribe learning media can improve online learning outcomes, namely (1) online learning outcomes for knowledge KD have increased by 24.42%, while online learning outcomes for skills KD have increased by 23.47%. In addition, the level of completeness of students has increased. The increase in mastery of KD knowledge students is 37.36%, while the increase in mastery of KD skills students is 53.59%. ABSTRAKInteraksi dalam pembelajaran daring sangat terbatas sehingga pendidik harus bisa kreatif dan inovatif memilih media pembelajaran, khususnya dalam mata pelajaran Bahasa Indonesia agar dapat meningkatkan hasil belajar peserta didik di rumah. Penerapan media pembelajaran videoscribe dalam pembelajaran daring Bahasa Indonesia merupakan salah satu pemanfaatan teknologi media pembelajaran berbasis animasi yang sesuai dengan perkembangan zaman sehingga diharapkan dapat meningkatkan mutu pendidikan. Tujuan best practice ini adalah untuk mendeskripsikan pemanfaat media pembelajaran videoscribe sebagai alternatif pembelajaran daring Bahasa Indonesia kelas XI di SMKN 1 Cangkringan. Praktik terbaik dilakukan pada bulan November, Semester Ganjil Tahun Ajaran 2020/2021 dengan subyek penelitian sejumlah 66 siswa. Tujuan karya tulis ilmiah ini untuk mendeskripsikan peningkatan hasil belajar dengan memanfaatkan teknologi media pembelajaran videoscribe sebagai alternatif media pembelajaran daring pada mata pelajaran Bahasa Indonesia. Penerapan media pembelajaran videoscribe dapat meningkatkan hasil belajar daring yaitu (1) hasil belajar daring KD pengetahuan mengalami peningkatan sebesar 24,42%, sedangkan peningkatan hasil belajar daring KD keterampilan sebesar 23,47%. Selain itu, tingkat ketuntasan peserta didik mengalami peningkatan. Peningkatan ketuntasan peserta didik KD pengetahuan sebesar 37,36%, sedangkan peningkatan ketuntasan peserta didik KD keterampilan sebesar 53,59%.